2014
DOI: 10.1098/rspa.2014.0408
|View full text |Cite
|
Sign up to set email alerts
|

Lévy flight movement patterns in marine predators may derive from turbulence cues

Abstract: The Lévy-flight foraging hypothesis states that because Lévy flights can optimize search efficiencies, natural selection should have led to adaptations for Lévy flight foraging. Some of the strongest evidence for this hypothesis has come from telemetry data for sharks, bony fish, sea turtles and penguins. Here, I show that the programming for these Lévy movement patterns does not need to be very sophisticated or clever on the predator's part, as these movement patterns would arise naturally if the predators ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…By looking with fresh eyes we can make unexpected discoveries and connections that others have missed. Surprising connections have already been made: between Zipf's law for city sizes and the occurrence of Lévy searching patterns in honeybees [98]; between turbulence theory and Lévy flights in marine predators [97]; between the Movement Ecology Framework and Lévy flights in atomic vapours, even in interstellar space [179]; between passive aerial dispersal and analyses of on-line gaming strategies [79]; between effective searching for and within patches [121]; between percolation and Lévy walking. More surprises are likely to be in store as we make further advances.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…By looking with fresh eyes we can make unexpected discoveries and connections that others have missed. Surprising connections have already been made: between Zipf's law for city sizes and the occurrence of Lévy searching patterns in honeybees [98]; between turbulence theory and Lévy flights in marine predators [97]; between the Movement Ecology Framework and Lévy flights in atomic vapours, even in interstellar space [179]; between passive aerial dispersal and analyses of on-line gaming strategies [79]; between effective searching for and within patches [121]; between percolation and Lévy walking. More surprises are likely to be in store as we make further advances.…”
Section: Discussionmentioning
confidence: 98%
“…This apparent discrepancy between observations and expectations puts strain on the Lévy flight foraging hypothesis. This is resolved by invoking the new hypothesis because, under this scenario, Lévy flights are an emergent property of a natural response to turbulence [97].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a number of studies have shown that characteristics of LFs and LWs may emerge naturally on large scales from more realistic case specific models of movement [45], including simple deterministic and semideterministic walks in complex environments [35,[46][47][48][49][50], self-avoiding random walks [51][52][53], diffusion with a timevarying diffusion constant [54][55][56], and a multiplicative, selfaccelerating process [9,57,58]. It has also been suggested that in some species a power-law distribution of lengths of straight line segments of their movement patterns, a hallmark of LWs and LFs, is a consequence of either the Weber-Fechner law in odometry [59], a power-law distribution of switching times between competing activities [60][61][62][63][64][65], or a so-called aerial lottery [66][67][68].…”
mentioning
confidence: 99%